18F-DCFBC Prostate-Specific Membrane Antigen–Targeted PET/CT Imaging in Localized Prostate Cancer: Correlation With Multiparametric MRI and Histopathology. (October 2017) - Turkbey, Baris; Mena, Esther; Lindenberg, Liza; Adler, Stephen; Bednarova, Sandra; Berman, Rose; Ton, Anita T.; McKinney, Yolanda; Eclarinal, Philip; Hill, Craig; Afari, George; Bhattacharyya, Sibaprasad; et al.
Abstract : Purpose: To assess the ability of (N-[N-[(S)-1, 3-dicarboxypropyl]carbamoyl]-4- 18 F-fluorobenzyl-L-cysteine) ( 18 F-DCFBC), a prostate-specific membrane antigen–targeted PET agent, to detect localized prostate cancer lesions in correlation with multiparametric MRI (mpMRI) and histopathology. Methods: This Health Insurance Portability and Accountability Act of 1996–compliant, prospective, institutional review board–approved study included 13 evaluable patients with localized prostate cancer (median age, 62.8 years [range, 51–74 years]; median prostate-specific antigen, 37.5 ng/dL [range, 3.26–216 ng/dL]). Patients underwent mpMRI and 18 F-DCFBC PET/CT within a 3 months' window. Lesions seen on mpMRI were biopsied under transrectal ultrasound/MRI fusion–guided biopsy, or a radical prostatectomy was performed. 18 F-DCFBC PET/CT and mpMRI were evaluated blinded and separately for tumor detection on a lesion basis. For PET image analysis, MRI and 18 F-DCFBC PET images were fused by using software registration; imaging findings were correlated with histology, and uptake of 18 F-DCFBC in tumors was compared with uptake in benign prostatic hyperplasia nodules and normal peripheral zone tissue using the 80% threshold SUVmax. Results: A total of 25 tumor foci (mean size, 1.8 cm; median size, 1.5 cm; range, 0.6–4.7 cm) were histopathologically identified in 13 patients. Sensitivity rates of 18 F-DCFBC PET/CT and mpMRI were 36% and 96%, respectively, for all tumors. For index lesions, the largest tumor with highest Gleason score, sensitivity rates of 18 F-DCFBC PET/CT and mpMRI were 61.5% and 92%, respectively. The average SUVmax for primary prostate cancer was higher (5.8 ± 4.4) than that of benign prostatic hyperplasia nodules (2.1 ± 0.3) or that of normal prostate tissue (2.1 ± 0.4) at 1 hour postinjection ( P = 0.0033). Conclusions: The majority of index prostate cancers are detected with 18 F-DCFBC PET/CT, and this may be a prognostic indicator based on uptake and staging. However, for detecting prostate cancer with high sensitivity, it is important to combine prostate-specific membrane antigen PET/CT with mpMRI. Abstract : Supplemental digital content is available in the text.